Measuring Job Satisfaction Between Transformational Leadership and Organizational Citizenship Behavior (OCB) in the Banking Sector - Novianti, Khusnul Rofida; Roz, Kenny (Management Institute Faculty of Economics Universitas Andalas, 2023)
Organisational Citizenship Behaviour (OCB) is essential for promoting teamwork, excellent customer service, and organizational performance in the banking industry. Its relationship to transformational leadership styles fosters a culture of trust, innovation, and job satisfaction in addition to motivating staff to go above and beyond the call of duty, enhancing overall performance and experience. This research focuses on the role of job satisfaction in mediating the effect of transformational leadership on organizational citizenship behavior (OCB) in the employees of the banking sector in Malang City, East Java. Using a questionnaire as a research instrument, 118 responses were analyzed using partial least square (PLS) software. The result of this study revealed that transformational leadership and job satisfaction have a significant effect on OCB. Job satisfaction has a significant effect on OCB both directly and indirectly and can be mediating the effect of transformational leadership on organizational citizenship behavior (OCB).